2003
DOI: 10.1109/twc.2003.814345
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exponential backoff scheme and retransmission cutoff on the stability of frequency-hopping slotted ALOHA systems

Abstract: The combinatorial effect of an exponential backoff scheme and retransmission cutoff on the stability of frequencyhopping slotted ALOHA systems with finite population is investigated in terms of the catastrophe theory. In the systems, the packet retransmission probabilities are geometrically distributed with respect to the number of experienced unsuccessful transmissions and a packet will be discarded after a certain number of unsuccessful transmissions. Expressions which should be satisfied at equilibrium poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
10
1
1
Order By: Relevance
“…We have used Eqs. (6) and (10) to draw the Figure 6. This figure also shows that the finite number of retransmission trials improves the packet dropping probability at lower input traffic, which is a similar result as presented in [8,11,19].…”
Section: B Packet Rejection Probabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…We have used Eqs. (6) and (10) to draw the Figure 6. This figure also shows that the finite number of retransmission trials improves the packet dropping probability at lower input traffic, which is a similar result as presented in [8,11,19].…”
Section: B Packet Rejection Probabilitymentioning
confidence: 99%
“…Stability of frequency-hopped spread-spectrum random access (Slotted ALOHA) is studied in [10] considering the combined effect of exponential back-off and the number of retransmission trials. The stability and the maximum throughput of retransmission cut-off Slotted ALOHA can also be increased using multiple power levels [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that system stability can be achieved by controlling the retry limit and the channel coding rate that affects the transmission success rate of a packet. Sakakibara et al examined the exponential backoff (EB) algorithm with retry limit in slotted (S)-ALOHA systems [4] and frequency-hopped S-ALOHA systems [5], respectively. Additionally, Liu [6] examined an EB algorithm in frequency-hopped S-ALOHA systems under a finite population with unsaturated traffic (FP/UST) model.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Falla et al [8], Vu et al [9], and Chuck et al [10] examined window-based BEB with retry limit for an IEEE 802.16 system under FP/ST. It should be noted that the S-ALOHA system under the FP/ST model always operates in a stable but inefficient region [4], [5]. In contrast to [7]- [10] with the FP/ST model, in this paper, we examine the performance of UB and BEB algorithms with retry limit under a more realistic FP/UST model and discuss their stability.…”
Section: Introductionmentioning
confidence: 99%